Frailty and spatialization of older adults in the city of Uberlândia with IVCF-20 - Rubia Pereira Barra; Edgar Nunes de Moraes; Maria Margaret de Vasconcellos Lemos; Poliana Castro de Resende Bonati; José Flávio Morais Castro; André Augusto Jardim (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To describe the functional clinical profile of elderly people linked to primary health care, using the Functional Clinical Vulnerability Index (IVCF-20) and to spatialize those with the greatest functional decline by primary health care units in the municipality of Uberlândia, in the state of Minas Gerais (MG), in the year 2022. METHODS A cross-sectional study with secondary data from the Municipal Health Department of Uberlândia-MG. The variables were compared using Student's t-test, Mann Whitney test, Pearson's chi-square, and multinomial logistic regression to obtain the independent effect of each variable. The significance level adopted was 5% (p < 0.05). The georeferenced database in ArcGIS® was used. RESULTS 47,182 older adults were evaluated with a mean age of 70.3 years (60 to 113 years), 27,138 of whom were women (57.52%), with a clear predominance of low-risk or robust older adults (69.40%). However, 11.09% are high-risk older adults and 19.52% are at risk of frailty. Older men had independently lower odds of moderate and high risk compared to older women (OR = 0.53; p < 0.001). A high prevalence of polypharmacy was observed, 21.40% of the older adult population, particularly in frail older adults, with a prevalence of 63.08%. There was a greater distribution of frail older adults around the central region of the municipality and in health units with a larger coverage area. The IVCF-20 made it possible to screen frailty in primary health care. CONCLUSION The instrument is capable of stratifying the risk of older adults in health care networks through primary health care, enabling the application of individualized preventive, promotional, palliative, or rehabilitative interventions, according to the clinical functional stratum of the older adult and the compromised functional domains. Risk stratification and spatial distribution of the frailest older adults can be a good strategy for qualifying health professionals with the aim of maximizing the autonomy and independence of the older adults.